Impact of Artificial Intelligence on Islamic Education: Effectiveness, Innovation, and Socio Cultural Influence - M Agus Salim; Nurlaila Rajabiyah (Inovasi Analisis Data, 2025)
Objective: This study discusses the role of AI in Islamic education, from the aspects of effectiveness, innovation in learning, and socio-culture. This study includes how artificial intelligence allows better learning for the students, innovative teaching methods, and social and cultural change in Islamic education.Methods: This research is a meta-analysis that aims to synthesize data from several studies related to the application of AI in Islamic education. Cohen’s d was used to compute the effect size quantifying the effect of AI on learning deviations learning effectiveness, learning innovation, and learning socio-culture.Results: The results show that AI has moderate but significant impact on Islamic education. The most influential factors are socio-cultural factors (the influences of social factors) and recent educational innovative reforms (innovation), followed by learning effectiveness (focusing on adaptive learning and the connectedness of the learning environment). The findings provide evidence that the incorporation of AI is beneficial for enhancing learning outcomes and facilitating cultural and social transformation in the context of Islamic education.Novelty: This research sheds light on the effects that AI can have on Islamic education, and presents a unique take on the issue, focusing on improving learning outcomes, and capturing innovation in the socio-cultural context. It also calls for more research into how external forces access to technology, teacher involvement, community buy-in can shape this work.Theory and Policy Implications: The results affirm the importance of integrating AI into Islamic education and recommend that policymakers focus on AI-based projects that align with local cultural contexts and technological capacity. It is recommended in the study to customise the operation of AI-based learning solutions according to general Islamic educational values and the needs of students. Additional studies are needed to capture the broader ramifications of AI on educational policies and practices in different socio-cultural contexts.